Experimental and thermodynamic assessment of the Co–Gd–Ti system. (September 2016) - Mattern, N.; Zinkevich, M.; Han, J.H.; Löser, W.
Abstract: The ternary phase diagram Co–Gd–Ti was experimentally assessed. An isothermal section at T =773 K is presented. The phase equilibria for Co-contents <70 at% are characterized by the coexistence of the binary terminal phases with low solubility of the respective third element. For higher Co-contents one ternary phase GdCo12− x Ti x (S.G. I4/mmm) exists with a homogeneity range of 1≤ x ≤2. The liquid phase of the ternary system exhibits a miscibility gap originating from the binary Gd–Ti subsystem, which extends beyond 30 at% Co. Based on the experimental data, a thermodynamic description is derived. Graphical abstract: Highlights: The Co–Gd–Ti phase diagram is experimentally assessed. An isothermal section at T= 773 K is presented. The ternary phase GdCo12− x Ti x has a homogeneity range of 1≤ x ≤2. The miscibility gap of the Gd–Ti liquid extends beyond 30 at% Co. A thermodynamic description of the Co-Gd–Ti system is derived.